The meaning and relevance of internal market orientation in nonprofit organisations. Issue 5 (26th April 2018) - Modi, Pratik; Sahi, Gurjeet Kaur
ABSTRACT: A large number of nonprofit organisations (NPOs) deliver welfare services in developing countries. Many find it difficult to retain their staff and to increase beneficiary satisfaction, which negatively affect their mission achievement activities. This research shows that internal market orientation (IMO) can help field-based NPOs address the managerial challenges. Towards this end, this research validates Lings and Greenley's [(2005). Measuring internal market orientation. Journal of Service Research, 7(3), 290–305.] scale to measure IMO in field-based NPOs and establishes IMO's relevance for them. Data from 370 NPOs were analysed using confirmatory factor analysis to validate the IMO construct in the nonprofit context, and structural equation modelling to show that IMO improves beneficiary satisfaction and staff retention rates in NPOs. The study enhances our understanding of IMO in NPOs and offers important managerial implications.